Prevalence and distribution of sesamoid bones of the hand in Omani subjects: a radiological study - Al Khabori, Hussein; Al Asmi, Maitha; Sirasanagandla, Srinivasa Rao; Al Rashdi, Firas; Al Dhuhli, Humoud; Jaju, Sanjay; Al Mushaiqri, Mohamed (Anatomical science international, 2021)
Sesamoid bones show considerable variations in their occurrence among various ethnicities. This study aims to evaluate the prevalence and distribution patterns of the sesamoid bones of the hands among Omani patients who were referred for radiological investigations. The influence of gender and different age groups on the occurrence of sesamoid bones of the hand was determined using the Chi-square test. Spearman’s rank correlation was used to determine the coexistence of sesamoid bones at the metacarpophalangeal joints. A total of 541 hand radiographs were reviewed. A high prevalence of sesamoid bones at the fifth metacarpophalangeal joint and the interphalangeal joint of the thumb was noted with a frequency of 64% and 49.7%, respectively. There were ten different patterns of sesamoid bones detected, the most common of which was the presence of sesamoid bones at the first and fifth metacarpophalangeal joints found in 32.9% of the radiographs. A statistically significant gender difference was observed at the interphalangeal joint of the thumb ( p = 0.025) and fifth metacarpophalangeal joint ( p = 0.027) with a female dominance. A significant association between the age and prevalence of sesamoid bones was noted at the fifth metacarpophalangeal joint ( p = 0.03). The prevalence of the sesamoid bones of the hand in Omani subjects seems to differ from other Middle Eastern populations, particularly at the fifth metacarpophalangeal joint and the interphalangeal joint of the thumb. In the meantime, the baseline data of our study can be helpful while treating the patients complaining of hand discomfort or pain.